ADOLESCENT CRISIS AND EDUCATIONAL CRISES OF ADAPTATION TO THE NEXT EDUCATIONAL LEVEL - Leonova, Elena V. (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The problem of pupils’ adaptation to new educational level is explored from the standpoint of human agency becoming.194 pupils (84 fifth-graders and 110 tenth-graders) took part in the study. Pupils’ agency and psychological resources were surveyed at the beginning of the academic year by Children’s Personality Questionnaire (CPQ), Pupils’ Motives Questionnaire (fifth-graders), High School Personality Questionnaire (HSPQ), Purpose-in-Life Test, Motives of learning activity Questionnaire (tenth-graders). Adaptation criteria (informational, behavioral and affective) were estimated by expert assessment method and academic performance analysis at the end of the academic year. K-means method of cluster analysis, U-test and Spearman's rank correlation coefficient are used for data analysis.In each age category of pupils we have found a lot of significant correlation links between the psychological resources and adaptation criteria indicators only in the cluster of pupils with high agency level. So, only pupils with a high level of agency use their psychological resources to successful overcoming of normative educational crises. Thus, without human agency qualities, both the intellectual and personal resources of pupils can remain unused during the period of adaptation and further training, the results of the study demonstrated.The study was funded by RFBR, project # 18-413-400001